‘HydroAR’: An Innovative Augmented Reality Learning Media for Water Cycle Material in Elementary School - Rochmah, Eliya; Jannah, Widia Nur; Rahayu, Fanny Septiani; Yulianawati, Dewi; Zain, Farah Mohamad; Islamulmuflikhun, Alifsyam (Profesi Pendidikan Dasar, 2025)
The water cycle is a fundamental science topic in primary education; however, its abstract and dynamic processes are often difficult for students to understand, highlighting the need for interactive learning media that can visualize concepts clearly. The primary objective of this study was to develop and evaluate the feasibility and effectiveness of HydroAR, an AR-based learning medium, in improving primary students’ understanding and interest in the water cycle. Utilising the 4D Research and Development (R&D) model comprising the Define, Design, Develop, and Disseminate stages. The research involved a limited-scale pilot study with 22 students and one teacher, followed by a wider dissemination trial involving 30 students in Cirebon Regency. Data were collected via material and media expert questionnaires, alongside teacher and student response surveys, and were subsequently analysed using both quantitative and qualitative methods. HydroAR was successfully developed with interactive visualizations that made abstract concepts clearer and more engaging. Expert evaluations rated it as very feasible. Student usability results showed acceptable SUS scores of 83.18% and 85.58%. The implementation increased learning interest and improved water cycle understanding, indicating AR’s potential to support interactive teaching and effective science concept visualization.